An experience-based perspective on pro-environmental behavior in urban forests ecotourism - Sitti Nur Azmi Fadhlurrahmah; Karin Ayunia Chaerunisa (Privietlab, 2026)
Urban forest ecotourism has emerged as an important strategy for promoting sustainable tourism and pro-environmental behavior in rapidly urbanizing cities. However, there has been limited attention to understanding how experiential encounters in urban forests translate into pro-environmental behavioral intentions. Drawing on the Theory of Planned Behavior (TPB) and Experience Economy Theory, this study examines the relationships among experience quality, perceived value, attitude, and pro-environmental behavioral intention in the context of urban forest ecotourism. A quantitative research design was employed using a cross-sectional survey of 460 urban forest visitors. Data were analyzed using Structural Equation Modeling with a variance-based approach (SEM-PLS) to assess both the measurement and structural models. The results indicate that experience quality has significant positive effects on perceived value and attitude. Furthermore, both perceived value and attitude significantly influence pro-environmental behavioral intention. However, the direct effect of experience quality on pro-environmental behavioral intention was not significant, suggesting that experiential encounters influence intention indirectly through cognitive and attitudinal mechanisms. These findings extend the TPB framework by demonstrating that experience quality functions as a formative antecedent of attitude and perceived value rather than a direct predictor of pro-environmental intention. The study highlights the importance of designing meaningful urban forest experiences that foster positive evaluations and attitudes toward sustainability. From a managerial perspective, the results provide practical insights for urban forest managers and policymakers seeking to enhance pro-environmental outcomes through experience-based ecotourism strategies.